2021
DOI: 10.1177/10556656211042168
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Use of Ketorolac Improves Pain Management and Decreases Narcotic Use Following Primary Cleft Palate Surgery

Abstract: Objective To study the efficacy and safety profile of ketorolac in cleft palate surgery. Design Retrospective analysis of patients who underwent primary cleft palate surgery and received either postoperative ketorolac or opioids. Setting Tertiary care children's hospital. Patients, Participants Eighty-nine patients enrolled who were all younger than 36 months of age, not dependent on a gastrostomy tube, with no history of bleeding disorders, and had undergone their primary cleft palate procedure by one specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…13 While studies report mixed results regarding the efficacy of ketorolac in reducing postoperative pain and narcotic usage in palatoplasty patients, Dudley et al found that ketorolac decreased narcotic usage and postoperative pain scores. 29,30 Multidisciplinary teams may want to consider the incorporation of ketorolac in their ERAS protocols as well.…”
Section: Patient Safetymentioning
confidence: 99%
“…13 While studies report mixed results regarding the efficacy of ketorolac in reducing postoperative pain and narcotic usage in palatoplasty patients, Dudley et al found that ketorolac decreased narcotic usage and postoperative pain scores. 29,30 Multidisciplinary teams may want to consider the incorporation of ketorolac in their ERAS protocols as well.…”
Section: Patient Safetymentioning
confidence: 99%
“…Studies investigating the topic of pain and analgesia were the most common (n=31; Supplemental Table 5, Supplemental Digital Content 5, http://links.lww.com/SCS/E642)12,13. Many of the included studies investigated the use of various analgesia techniques that aimed at reducing postoperative opioid consumption 2,14–29. Seven of the included studies investigated the effectiveness of bupivacaine for use in nerve block in cleft lip and/or palate repair 1,4,28,30–33.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the included studies investigated the use of various analgesia techniques that aimed at reducing postoperative opioid consumption. 2,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Seven of the included studies investigated the effectiveness of bupivacaine for use in nerve block in cleft lip and/ or palate repair. 1,4,28,[30][31][32][33] All but 1 1 focused on infraorbital nerve block placement in cleft lip surgery patients.…”
Section: Pain and Analgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, another recent retrospective study similarly showed that the use of ketorolac in patients undergoing total cranial vault remodeling did not lead to significant postoperative bleeding events requiring transfusion 12 . In contrast, Dudley et al 13 reported 1 bleeding event in their retrospective study of patients treated with ketorolac after primary cleft palate repair; this adverse event occurred in a patient with multiple congenital anomalies and was treated with a topical hemostatic agent. In our small cohort of patients receiving ketorolac, no postoperative bleeding complications leading to transfusion of blood products or unplanned return to the OR were recorded.…”
Section: Discussionmentioning
confidence: 99%